Engineering of spectator glycocalyx structures to evaluate molecular interactions at crowded cellular boundaries. (17th July 2019) - Honigfort, Daniel J.; Zhang, Michelle H.; Verespy, Stephen; Godula, Kamil
Abstract : Membrane engineering with bystander glycocalyx structures reveals altered protein–receptor association in crowded cell surface environments. Abstract : In the mucosal epithelium, the cellular glycocalyx can project tens to hundreds of nanometers into the extracellular space, erecting a physical barrier that provides protective functions, mediates the exchange of nutrients and regulates cellular interactions. Little is understood about how the physical properties of the mucosal glycocalyx influence molecular recognition at the cellular boundary. Here, we report the synthesis of PEG-based glycopolymers with tunable glycan composition, which approximate the extended architecture of mucin glycoproteins, and tether them to the plasma membranes of red blood cells (RBC) to construct an artificial mucin brush-like glycocalyx. We evaluated the association of two lectins, ConA and SNA, with their endogenous glycan ligands on the surface of the remodelled cells. The extended glycocalyx provided protection against agglutination of RBCs by both lectins; however, the rate and magnitude of ConA binding were attenuated to a greater degree in the presence of the glycopolymer spectators compared to those measured for SNA. The different sensitivity of ConA and SNA to glycocalyx crowding likely arises from the distinct presentation of their mannoside and sialoside receptors, respectively, within the native RBC glycocalyx.